PROFESIONALISME GURU TERHADAP KARAKTER SISWA DI MI SUNAN KALIJOGO, KELURAHAN KARANGBESUKI, KECAMATAN SUKUN, KOTA MALANG - Yusyrotur Rodliyah; Anwar Sa’dullah; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstrakTeacher's profession is a job that has special expertise, where many people don't have. Whereas to be a professional teacher can be achieved with indicators including being able to prepare all the needs of planning, implementation, evaluation and assessment that are in accordance with the objectives of the institution. In schools that have professional teachers with high indicator values, then in the category of experts educate students, especially holding different student characters. Discussing the character of students is very closely related to cognitive value in number two, right. So it is very important, the morals of students who must be fostered if there are less good and make it better than before. This research was conducted at MI Sunan Kalijogo, Karangbesuki, Sukun, Malang City. The researcher used quantitative research with the type of associative research using a survey approach. Intends to find the relationship of teacher professionalism (Variable X) to the character of students (Y). With the results according to the data that rxy = 0.96 which indicates a very strong relationship between teacher professionalism towards the character of students.Keyword: professionalism teachers, student characters